What are the priorities for future success in critical care research in the UK? Report from a national stakeholder meeting. (November 2015) - Walsh, Tim; Brett, Stephen J
Critical care in the United Kingdom is now well-established in terms of professional status, standards of clinical practice and training, and national audit through professional bodies and government representation. Research is fundamental to the further development and maturation of the specialty, to develop new therapies and technologies, more efficient and effective service organisation, and to improve patient and family experience and outcomes. Critical care research has expanded rapidly in the UK, and now has established organisations and infrastructure to share and develop ideas, through the UK Critical Care Research Forum and similar meetings. In September 2014, the Intensive Care Foundation and Critical Care Leadership Forum hosted a research colloquium to reflect, in part, on achievements, but more importantly plan for the future. With an invited list of participants the meeting explored firstly – the practical delivery of clinical research and secondly – the future financing landscape, from both academic funders' and commercial developers' perspectives. The following article summarises the important 'take home' messages from this meeting and suggests key issues for future strategy.